Estilo tomboy: a moda feminina masculinizada - Santos, Letícia Arruda dos (2015)
The present work aims to attend the necessities of women that identify themselves with clothing masculine aesthetically and also aim to minimize the stereotype associated with this way of dressing and homossexuality, after all, the preference for this style is independent of the sexual orientation. For that was made a bibliographic research which was studied fashion and identity, exposing how the body is used to interpersonal communication and how the fashion is also a way of communication and of representation of the person. Was made researches about gender, talking about general concepts and aplied to fashion, was also studied about tomboy¹. The process of absorbing of masculine character by the feminine clothing through the history is presented in chapter 2.3. Concludes the fundamentation with facts of XXI century fashion. Used as methodology the documental research, and for this work was used specifically the images analysis, in order to study the aesthetics preferences of the chosen public, that are woman that adopt a masculine style when dressing and adorn themselves.Was selected 88 images from the website Tumblr, and analysed each one individually; after that was elaborated the brand Slick Rain. The collection spring/summer 2016 was based in fashion and life style of the nineties.